Determinación del potencial turístico de la Comunidad Nativa Huitoto Murui Bue “centro arenal”, Distrito de Punchana, Departamento de Loreto - Saldaña Cardenas Rubi Celeste (2024)
In the thesis “Determination of the tourism potential of the native Huitoto Murui Bue community “Arenal center”, Punchana district, Loreto department”, the natural and semi-natural resources of the place were investigated. It was investigated under the quantitative approach, a survey and questionnaire were applied to obtain results of the indicators: natural sites, folklore, land management and type of demand. On the other hand, a structured observation was applied, to complement the data of the quantitative research. The population is 120 families and 30% was considered for the sample (1 respondent per family), totaling 36 respondents. It was applied to the inhabitants who have natural and semi-natural resources, the same ones who have income from the demonstration effect of their resources. According to the results, natural sites, like accessibility, are an advantage; in addition, the waterfalls have clean water that serves as a landscape and also for drinking. Folklore, music, gastronomy, myths and legends are significant. Territory management refers to the degree of knowledge of the tourist potential and the marketing of services and products to improve the economy of the inhabitants who carry out certain activities. The type of demand is significant to improve living conditions with tourism, increase identity and culture, among others. The hypothesis was accepted, since the natural and semi-natural resources of the Huitoto Murui Bue